Political Informality on Social Media: The Impact of Influencer Involvement in the Central Sulawesi Gubernatorial Election Contest on the Institutionalization of Democracy - Fitriningsih; Sunardi; Sitti Rabiatul Wahdaniyah Herman (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
This research will examine the relationship between the state and citizens mediated by social media. It examines two social contexts: first, the digital revolution, which has driven the trend of increasing social media use, and second, the high level of interaction on social media, which has created space for the presence of informal third parties. These third parties take the form of